2007 Minneapolis, Minnesota, June 17-20, 2007 2007
DOI: 10.13031/2013.23242
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Passively-Aerated Plastic-Wrapped Composting System Designed for Emergency Disposal of Swine Mortalities

Abstract: Monitoring of a passively-aerated plastic-wrapped mortality composting system designed for emergency disposal of diseased swine highlighted the importance of the physical characteristics of materials used to envelop the carcasses. Inadequate moisture was a problem when using envelope materials such as ground cornstalks or straw having low density and high air-filled porosity. High O 2 concentrations throughout these materials, and significantly higher moisture levels in the top layers than in the materials sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…This zone is remarkable in the fact that it is so highly compacted that it is difficult to penetrate the layer, even with a small spade. This is consistent with findings by Ahn et al (2007Ahn et al ( , 2008, Glanville et al (2007), and Schaub-Szabo and Leonard (1999). It was also 'stickier' and held together more than other layers.…”
Section: Compacted Zonesupporting
confidence: 92%
See 2 more Smart Citations
“…This zone is remarkable in the fact that it is so highly compacted that it is difficult to penetrate the layer, even with a small spade. This is consistent with findings by Ahn et al (2007Ahn et al ( , 2008, Glanville et al (2007), and Schaub-Szabo and Leonard (1999). It was also 'stickier' and held together more than other layers.…”
Section: Compacted Zonesupporting
confidence: 92%
“…Ahn, et al (2007) and Glanville et al (2007) reported on a study in which swine carcasses were composted inside a plastic wrapped pile. Moisture levels were checked at the top, middle, and bottom of the test piles.…”
Section: Pile Structure and Zone Differences In Carcass Compost Pilesmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, Pollard et al (2008) included contained composting as one of the most desirable options for carcass disposal in a recent risk assessment of exposure to AI. Biosecure composting has also been used as a means of disposing of swine carcasses (Ahn et al, 2007; Glanville et al, 2007) although to date biocontainment composting has not been assessed for its ability to dispose of carcasses arising from disease outbreaks in cattle.…”
mentioning
confidence: 99%
“…The effectiveness of mortality composting systems for the disposal of mass mortalities during catastrophic or emergency situations has been reported in previous papers (Benfeldt et al, 2006;Glanville et al, 2007;Glanville, 2006b;Spencer et al, 2004). These papers outline the ability of mortality composting to be adapted to handle a large volume of mortalities, utilizing a variety of systems and envelope materials.…”
Section: Compostingmentioning
confidence: 54%